Analysis of the Impact of Yogyakarta International Airport (YIA) on the Financial Independence of Kulon Progo Regency - Srimaryani; Muhammad D (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the impact of YIA's existence on the financial independence of Kulon Progo Regency during three different time periods, namely the pre-COVID period (2018-2019), the Community Activity Restrictions (PPKM) period (2020), and the period entering the new normal era (2020). 2021-2022). The approach used in this research is through regional financial ratio analysis with a focus on taxes and levies. The research results show that the existence of YIA has a significant impact on tax and retribution revenues in Kulon Progo Regency. The results of this research provide a better understanding of the impact of YIA's existence on regional finances and can be used as a basis for making better policy decisions in the future